2014
DOI: 10.1080/13597566.2013.877449
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes to Gaelic and the Debate about Scottish Autonomy

Abstract: Scotland seems to be a counter-example to general theories of the relationship between language and national identity or nationalism. These theories point to three components in the ideology of language and nation -that being able to speak the national language is necessary for full national membership, that the national language is a core part of the nation's culture, and that the future of national political autonomy and the future of the national language are connected with each other. In Scotland, it has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Furthermore, approximately two‐fifths of respondents stated that Gaelic was important for their sense of national identity (Scottish Government ). This reflects similar attitudes that have been found in previous studies on attitudes towards Gaelic (MacKinnon ; Paterson et al ). These surveys show that it is possible for non‐speakers of a language to have positive affect towards that language and also claim it as a symbol of their own national identity.…”
Section: Literature Reviewsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, approximately two‐fifths of respondents stated that Gaelic was important for their sense of national identity (Scottish Government ). This reflects similar attitudes that have been found in previous studies on attitudes towards Gaelic (MacKinnon ; Paterson et al ). These surveys show that it is possible for non‐speakers of a language to have positive affect towards that language and also claim it as a symbol of their own national identity.…”
Section: Literature Reviewsupporting
confidence: 89%
“…Though both Gaelic and Scots are historically important heritage languages in Scotland, Gaelic seems to be most recently emphasised as being associated with ‘Scottishness’ . Paterson et al () found a positive association between views about Gaelic and feelings of Scottish identity. Taken one step further, these feelings of ‘Scottishness’ can manifest themselves into a political identity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…on people who oppose it was identified. A general lack of awareness of Gaelic in wider Scottish society has been observed to co-exist with moderately positive attitudes (MacCaluim 2007;Paterson et al 2014) but the extent of this unawareness among adults educated through…”
Section: 'Snobbery'mentioning
confidence: 99%
“…Gaelic-medium (GM) education, including the preschool sector, is seen, not only by government policymakers but more generally by the Scottish public (Paterson, O'Hanlon, Ormston & Reid, 2014), to be an important element of the revitalisation plan for the language Pre-publication -forthcoming in Spring 2016 -Journal of Immersion and Content-Based Language Education 4:1 (2016), p 59-85 4 (Bòrd na Gàidhlig, 2012). Gaelic is a Celtic language, established in Scotland for at least 1500 years (Gillies, 1993), but now spoken by just over 1% (58,000 people) of the Scottish population (National Records of Scotland, 2013).…”
Section: Gaelic and Gaelic-medium (Gm) Preschool Provisionmentioning
confidence: 99%